In the Climate Emergency, Conservation Must Become Survival Ecology - Gardner, Charlie J.; Bullock, James M. (Frontiers in Conservation Science, 2021)
•Earth faces a climate emergency which renders conservation goals largely obsolete. •Current conservation actions are inadequate because they i) underplay biodiversity’s role in maintaining human civilisation, which contributes to its marginalisation, and ii) rely on false assumptions of how to catalyse transformative change. •We suggest a paradigm shift from biodiversity conservation to survival ecology, refocusing the field on safeguarding a planetary system in which humans and other species can thrive. •Rather than seeking to maintain a world which will no longer exist, survival ecology acknowledges unavoidable change and seeks to shape the world that will: it looks to the future, not the past. •Since conservation science and advocacy have not been sufficient to achieve the required change, survival ecologists should additionally embrace non-violent civil disobedience.